The Performance of Pivot-Type Trailer for Fresh Fruit Bunches Transport Equipment Using Two-Wheeled Tractors in Oil Palm Fields - Muhammad Idkham Idkham; Muhammad Dhafir Dhafir; Safrizal Safrizal Safrizal (The University of Lampung, 2023)
Poor farmers in Indonesia still transport palm fruit bunches manually, so they require a lot of manpower and many of them are transported for a long time, reducing quality. Oil palm farmers have two-wheeled tractors that are used for processing rice fields that can be used for towing trailers. The existing conventional trailers do not work optimally in oil palm fields, so it is necessary to design a pivot type trailer. The purpose of this study was to see the performance of the pivot type trailer for transporting oil palm fruit bunches, the pivot type trailer and the conventional one that was tested directly on the farmers' oil palm fields involving 3 operators. The results show that the pivot type trailer has an advantage over conventional trailers and is easy to operate properly, this is reflected in its very small turning radius of 260 cm unloaded and 280 cm loaded, and has a larger working capacity.Keywords: Pivot type trailers, Conveyances, Oil palm fields, Oil palm bunches,Smallholders. Pivot type trailers, Conveyances, Oil palm fields, Oil palm bunches, Smallholders.